Biphasic cuirass ventilation is better than bag-valve mask ventilation for resuscitation following organophosphate poisoning. (2015) - Gur, Ilan; Shapira, Shlomo; Katalan, Shahaf; Rosner, Amir; Baranes, Shlomo; Grauer, Ettie; Moran-Gilad, Jacob; Eisenkraft, Arik
Abstract: Objective: Exposure to organophosphates (OP) may lead to a life threatening cholinergic crisis with death attributed to a rapidly progressive respiratory failure. In a toxicological mass casualty event involving organophosphate exposure, many of the victims may depend on immediate short-term ventilation to overcome the respiratory distress which may exhaust life supporting resources. In addition, the mandatory use of personal protective gear by first responders emphasizes the need for a noninvasive, easy-to-operate ventilation device. Our objective was to assess the efficacy of MRTX, a Biphasic Cuirass Ventilation device, in comparison with standard bag-valve mask ventilation following acute organophosphate poisoning. Methods: Pigs were exposed to paraoxon poisoning (1.4 LD50 ), and treated 8 min later with atropine (0.05 mg/kg). The control group received no further support ( n = 9), the two experimental groups received ventilation support initiated 15 min post exposure and lasted for 25 min: one group was ventilated with the commonly used bag-valve mask (Mask group, n = 7) and the other was ventilated with the Biphasic Cuirass Ventilation device (Cuirass group, n = 7). Clinical signs and physiological parameters were monitored during the first hour, and mortality up to 24 h post exposure was recorded. Results: No mortality was observed in the Cuirass group following OP poisoning, while mortality in the Control and in the Mask groups was high (67% and 71%, respectively). Mouth excretions of the cuirass-ventilated animals were frothy white as in deep suctioning, as opposed to the clear saliva-like appearance of secretions in the other two groups. No further group differences were recorded. Conclusions: The noninvasive, easy-to-operate Biphasic Cuirass Ventilation device was effective in reducing OP-induced mortality and might be advantageous in an organophosphate mass casualty event. This finding should be validated in further investigations.